Structural and Nonstructural Proteins of Saint Louis Encephalitis Virus - Trent, Dennis W. (1971)
Analysis of purified Saint Louis encephalitis (SLE) virus by acrylamide gel electrophoresis revealed that the virions contained three structural proteins designated SP-1, SP-2, and SP-3 which had molecular weights of 63,000, 18,000, and 8,500, respectively. The envelope contained proteins SP-1 and SP-3 which were removed from the nucleocapsid by nonionic detergent treatment. Nucleocapsids prepared by deoxycholate treatment of complete virions had a density of 1.301 in potassium tartrate and contained SP-2 and SP-3. Brij-58-prepared SLE nucleocapsids had a density of 1.321 and contained only SP-2. Cycloheximide treatment for 1 hr in the presence of actinomycin irreversibly inhibited BHK cellular protein synthesis and reversibly inhibited the synthesis of SLE viral protein and ribonucleic acid. Three structural proteins and five virus-specific nonstructural proteins were detectable in SLE virus-infected BHK cells treated with actinomycin and pulse-inhibited with cycloheximide. Formation of each individual viral structural protein was detectable within 30 min after cycloheximide removal and continued with only minor changes from 12 to 18 hr after infection. Late in the infection cycle, synthesis of the nucleocapsid structural protein SP-2 and SP-3, the small envelope protein, was no longer detectable.